2002
DOI: 10.1152/ajplung.00188.2001
|View full text |Cite
|
Sign up to set email alerts
|

Human surfactant protein B promoter in transgenic mice: temporal, spatial, and stimulus-responsive regulation

Abstract: Surfactant protein B (SP-B) is a developmentally and hormonally regulated lung protein that is required for normal surfactant function. We generated transgenic mice carrying the human SP-B promoter (-1,039/+431 bp) linked to chloramphenicol acetyltransferase (CAT). CAT activity was high in lung and immunoreactive protein localized to alveolar type II and bronchiolar epithelial cells. In addition, thyroid, trachea, and intestine demonstrated CAT activity, and each of these tissues also expressed low levels of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 56 publications
0
8
0
2
Order By: Relevance
“…Three recent reports have assessed SP-B promoter activity in transgenic mice. A Ϫ1,039-to ϩ431-bp segment of the human SP-B promoter generated bronchoalveolar expression and low-level thyroid, trachea, and intestine expression (21). A separate study of the human SP-B promoter demonstrated that 1.5 kb directs lung and intestine expression in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Three recent reports have assessed SP-B promoter activity in transgenic mice. A Ϫ1,039-to ϩ431-bp segment of the human SP-B promoter generated bronchoalveolar expression and low-level thyroid, trachea, and intestine expression (21). A separate study of the human SP-B promoter demonstrated that 1.5 kb directs lung and intestine expression in mice.…”
Section: Discussionmentioning
confidence: 99%
“…AC109608). Furthermore, previous studies have established that a variety of human gene promoters are active in vivo using transgenic mice (2,24,37). Interestingly, the pattern of expression of the hSMVT promoter-luciferase transgene was found to be similar to that of the mouse endogenous SMVT message, especially in the different regions of the intestinal tract.…”
Section: Discussionmentioning
confidence: 84%
“…4A). 34,42, and 66 transgenic lines, confirming that the 4.3-kb Aqp5 promoter is only sufficient to drive high-level salivary gland-specific gene expression. 14, 34, 42, and 66) were identified.…”
Section: Identification Of Aqp5-egfp Transgenic Mice the Aqp5mentioning
confidence: 80%